2018
DOI: 10.3892/etm.2018.5695
|View full text |Cite
|
Sign up to set email alerts
|

In�vitro study on reversal of ovarian cancer cell resistance to cisplatin by naringin via the nuclear factor-κB signaling pathway

Abstract: Abstract. The aim of the present study was to investigate the mechanism of action by which naringin reverses the resistance of ovarian cancer cells to cisplatin. Semi-quantitative reverse transcription polymerase chain reaction (RT-PCR) and western blotting assays were used to detect the effects of different concentrations of naringin on the expressions of nuclear factor (NF)-κB and P-glycoprotein (P-gp) in the SKOV3/CDDP cell line. Small interfering RNA (siRNA) targeting NF-κB was designed and synthesized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…NF-κB is highly expressed in cisplatin-resistant ovarian cancer cell lines and has a crucial role in the drug resistance of ovarian cancer cells ( Choi et al, 2008 ). One study demonstrated that the inhibitory effect of naringin was associated with inhibition of the NF-κB signaling pathway, and treatment with naringin significantly reduced P-glycoprotein (P-gp) and NF-κB expression in a concentration-dependent way in SKOV3/CDDP cisplatin-resistant human epithelial ovarian cancer cell line ( Zhu et al, 2018 ). Another study also indicated that naringin downregulated COX-2 and NF-κB expression in a concentration-dependent way in SKOV3/CDDP cells ( Zhu et al, 2017 ).…”
Section: Anticancer Activities Of Naringinmentioning
confidence: 99%
“…NF-κB is highly expressed in cisplatin-resistant ovarian cancer cell lines and has a crucial role in the drug resistance of ovarian cancer cells ( Choi et al, 2008 ). One study demonstrated that the inhibitory effect of naringin was associated with inhibition of the NF-κB signaling pathway, and treatment with naringin significantly reduced P-glycoprotein (P-gp) and NF-κB expression in a concentration-dependent way in SKOV3/CDDP cisplatin-resistant human epithelial ovarian cancer cell line ( Zhu et al, 2018 ). Another study also indicated that naringin downregulated COX-2 and NF-κB expression in a concentration-dependent way in SKOV3/CDDP cells ( Zhu et al, 2017 ).…”
Section: Anticancer Activities Of Naringinmentioning
confidence: 99%
“…A few flavonoids, including naringin (Zhu et al, 2018) and taxifolin (Chen et al, 2018), have been identified as substrates of P-gp. The cellular uptake of 40 flavonoids was measured in parental human mouth epidermal carcinoma (KB) cells and KB/MDR cells with or without elacridar.…”
Section: Traditional Chinese Medicine Modulation Of P-gpmentioning
confidence: 99%
“…The mechanism of this activity may be related to regulation of the NF-κB signaling pathway. 6 In this study, we found that different concentrations of naringin inhibited the proliferation of SKOV3/CDDP cells in a time- and dose-dependent manner. After 20 µmol/L naringin treatment of SKOV3/CDDP-CN for 48 hours, the inhibition rate increased with increasing cisplatin concentrations compared with the 0-µmol/L naringin group (P < 0.05).…”
Section: Discussionmentioning
confidence: 58%
“…The reversal mechanism might be associated with the NF-κB pathway. 6 However, the exact mechanism of naringin in ovarian cancer cells remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%